Forms and Functional Repertoire of Acetylcholinesterase - Jiteesha V, Chavan; S. B., Donde (Journal of Neonatal Surgery, 2025)
Acetylcholinesterase is an enzyme that breaks down the bridge made in between the synaptic cleft by acetylcholine. This enzyme has neuronal as well as neuronal activity. Initially in this enzyme was known to be found only in invertebrates and vertebrates but in recent times we have found this in bacteria, algae, protozoa and primitive plants, suggesting its extremely early appearance in the course of evolution and a widespread expression in non-neuronal cells. There are two fractions when it comes to acetylcholinesterase one being a salt soluble form also called as a cytoplasmic form and a detergent soluble form can also be called as membrane bound form. The primary function ascribed to membrane bound fraction of AChE is pertaining to hydrolysis of acetylcholine at the cholinergic synapses as well as myoneural junctions, while salt-soluble or cytoplasmic fraction of enzyme is supposed to be involved in either cationic permeability or utilization of acetyl groups by excitable cells and therefore it is believed that this fraction of AChE might be associated with energy metabolism facets of cholinergic neurotransmission process. But the equally bountiful functional repertoire of its marker enzyme called acetylcholinesterase is in the light of pioneering research findings are reported from all the world over.